Communication—CMOS Thin-Film Transistors via Xe Flash-Lamp Crystallization of Patterned Amorphous Si. (1st January 2017) - Mudgal, T.; Bhadrachalam, K.; Bischoff, P.; Cormier, D.; Manley, R. G.; Hirschman, K. D.
Abstract : Flash-lamp annealing (FLA) has been investigated for crystallization of patterned amorphous silicon (a-Si) in the fabrication of NMOS and PMOS Thin-Film Transistors (TFTs) on display glass. Samples were exposed with a xenon flash irradiance of ∼30 kW/cm 2 and pulse duration of 200 μs, with bolometer measurements showing an integrated energy of ∼6 J/cm 2 . Non-self-aligned TFTs fabricated from the resulting polycrystalline silicon demonstrated electron and hole channel mobility values in excess of 300 cm 2 /(Vs) and 100 cm 2 /(Vs), respectively. According to the authors' knowledge, this is the first report of CMOS TFTs demonstrated using the FLA technique.